IMPLEMENTASI PROGRAM KESELAMATAN DAN KESESHATAN KERJA SERTA TANTANGAN YANG AKAN DIHADAPI PT PLN (Persero) PLTU TJB JEPARA DALAM UPAYA MEMPERTAHANKAN ZERO ACCIDENT - Pradana, Augusta Andhin; Djastuti, Indi (Diponegoro Journal of Management, 2015)
This study aimed to analyze the implementation of occupational safety and health program that runs in PT PLN (Persero) Unit PLTU TJB Jepara and identify constraints and challenges that will be faced by PT PLN (Persero) Unit PLTU TJB Jepara to maintain zero accident. This research was conducted using qualitative research methods, where researchers direct observation to the field that is in PT PLN (Persero) Unit PLTU TJB Jepara to know how the implementation of occupational safety and health program that is already running, and so far has reached zero accident. Data collected through interviews with the speakers who work in PT PLN (Persero) Unit PLTU TJB Jepara as well as secondary data from documents related to the implementation of safety and health in the PT PLN (Persero) Unit PLTU TJB Jepara. The results showed that the implementation of occupational safety and health program in PT PLN (Persero) Unit PLTU TJB Jepara went very well. For the constraints and challenges faced by PT PLN (Persero) Unit PLTU TJB Jepara related to the implementation of safety and health activities are followed up indiscipline of some employees related to the use of personal protective equipment and violations of the rules of safety and health such as smoking in the plant, with the making of a system sanctions for violators of safety rules and occupational health, as a means of controlling the enforcement of discipline. In terms of challenges, a form of socialization related to the rules and procedures for the safety and health of employees must be done by a variety of considerations level of education and social environment plural employees make the company must perform a different approach, so that the employees can receive and execute safety rules and health made by the company.